Konsep Tata Artistik pada Malva Makeup Artist - Ade, Aisya; Fauzi, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article discusses the concept of artistic makeup by Malva Makeup Artist, a professional in the makeup industry. The article explores how Malva Makeup Artist applies the principles of art, innovation, and uniqueness to create captivating and original makeup looks. It delves into the use of color, composition, arrangement, and creative techniques employed by Malva Makeup Artist. Additionally, the article highlights the exploration of current styles and trends, the creation of unique characters and themes, and the personalization of looks to emphasize each client's individuality. This article serves as a source of inspiration for professionals and makeup enthusiasts alike, offering insights on developing skills to create mesmerizing makeup looks